Effect of different clay materials made boccaro teapots on Oolong tea infusion quality - LI Xuan; KIM Eunhye; SHEN Yingbin; ZHANG Xiao; TU Youying; HE Puming (浙江大学学报. 农业与生命科学版, 2021)
The main chemical compositions of Oolong tea infusions brewed in three different clay materials (red clay, purple clay and Duan clay) made boccaro teapots were investigated and compared. Aroma components in the tea infusion were determined using headspace liquid-phase microextraction (HS-LPME) and gas chromatography-mass spectrometry (GC-MS), and their differences were compared through visual pattern recognition based on principal component analysis (PCA). The sensory evaluation was used to score the aroma, tea taste and infusion color. The results showed that the flavoring compound contents and water extraction of infusion brewed in the boccaro teapots were higher than those in the control group (beaker). The contents of water extraction were red clay pot＞purple clay pot＞Duan clay pot＞control group. Fresh and sweet substances such as amino acids and soluble sugar’s contents were relatively higher in the red clay pot. Substances which taste heavy, strong and bitter, such as tea polyphenols and caffeine’s contents were higher in the purple clay pot. There were more kinds of aroma components in boccaro teapots, including nerolidol, indole, linalool and its oxide, β-ionone and some other components with pleasant flower flavors. The proportions of different aroma components were significantly different from each other. The results of PCA showed that the comprehensive scores from high to low were red clay pot＞purple clay pot＞Duan clay pot＞control group. The red clay pot group was the best in enriching the aroma components with flower and fresh flavors. The results of sensory evaluation showed that the boccaro teapots could affect the Oolong tea in aroma, taste and infusion color. The comprehensive scores of sensory evaluation were red clay pot＞purple clay pot＞Duan clay pot.